Kearifan Teks Menyapa Konteks Mewujudkan Lokal Wisdom yang Rahmatan Li Al-'Alamin - Humaisi, Syafiq (FKIP Universitas Wisnuwardhana, 2021)
This article tries to dialogue the text in the form of the Qur'an and Hadith which is the result of the product of revelation with the context which is the result of dialogue between human life and the environment and society. This article formulates a more wise form of dialogue by placing text, addressing the context more so that a frame of local wisdom or soothing local wisdom can be realized. The pattern of reconstruction from Abou al-Fadle is an alternative choice in mediating texts with context, with the hope that the context will continue to be illuminated by the text so that existing local wisdom will continue to accompany a cool life in the peace of the text. As a result, several texts that were approached with the reconstruction of Abou al-Fadle in looking at the evolving context, turned out to be more responsive to various life problems such as discrimination, violence, gender bias and so on.